Decision-Making Accuracy And Its Relationship To Cognitive Achievement Of Football Law For Third-Year Students - Muhammad Jabran Abdulsahib; Mujtaba Salman Alawi (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Accuracy of decision-making is one of mental capabilities that contributes to overcoming competitors and working to make decision quickly to avoid wasting time during performance. Psychology is an important science that deals with psychological topics, including those related to sports activity in its various fields and levels. It also examines psychological characteristics and traits of personality that form subjective basis of sports activity, with aim of developing this type of activity and trying to find scientific solutions to its various applied problems. This research aims to identifying level of decision-making accuracy, identifying level of knowledge attainment in some football law subjects, identifying relationship between decision-making accuracy and cognitive achievement in some football law subjects for third-stage students. The research population was determined purposively and consisted of 77 in third-year students in Department of Physical Education and Sports Sciences at Al-Kut Private College for academic year 2024-2025. All students were selected to be research sample and the research sample constituted 100% of the research population. The researcher concluded that Students in Department of Physical Education and Sports Sciences have a high rate of quick decision-making, the students have a good level of knowledge attainment in subjects of football law, there is a direct relationship between students’ decision-making and their academic achievement. The researcher recommended that conducting other measures of the speed of decision-making among the research sample, conducting a comparison between male and female students regarding their decision-making level.